The impact of 1.5-T intraoperative magnetic resonance imaging in pediatric tumor surgery: Safety, utility, and challenges - Becerra, Victoria; Hinojosa, José; Candela, Santiago; Culebras, Diego; Alamar, Mariana; Armero, Georgina; Echaniz, Gastón; Artés, David; Munuera, Josep; Muchart, Jordi (Frontiers in Oncology, 2023)
Objective: In this study, we present our experience with 1.5-T high-field intraoperative magnetic resonance imaging (ioMRI) for different neuro-oncological procedures in a pediatric population and we discuss the safety, utility and challenges of this intraoperative imaging technology. Methods: A pediatric consecutive case series of neurooncological surgeries performed between February 2020 and May 2022 was analyzed from a prospective ioMRI registry. Patients were divided in four groups according to the surgical procedure: intracranial tumors (Group 1), intraspinal tumors (Group 2), stereotactic biopsy for unresectable tumors (Group 3) and catheter placement for cystic tumors (Group 4). Goal of surgery, the volume of residual tumor, preoperative and discharge neurological status, and postoperative complications related to ioMRI were evaluated. Results: 146 procedures with ioMRI were performed in this period. 62 of them were oncology surgeries: 45 in group 1; 2 in group 2; 10 in group 3; and 5 in group 4. The mean age of our patients was 8,91 years with the youngest being 12 months. ioMRI identified residual tumor and prompted further resection in 14% of the cases. Mean time for intraoperative image processing was 54 +/- 6 minutes. There were no intra- or postoperative security incidents related to the use of ioMRI. Reoperation rate in the early postoperative period was to 0%. Conclusion: ioMRI in pediatric neurooncology surgery is a safe and reliable tool. Its routine use maximizes the extent of tumor resection and did not lead to an increase of neurological deficits or complications in our series. The main limitations included the need for a strict safety protocol in a highly complex surgical environment, as well as inherent limitations for certain positions of patients with the available MR compatible headrests.